Comparative study of direct and indirect immunofluorescence and of bullous pemphigoid 180 and 230 enzyme-linked immunosorbent assays for diagnosis of bullous pemphigoid - Sárdy, Miklós; Kostaki, Dimitra; Varga, Rita; Peris, Ketty; Ruzicka, Thomas (Journal of the American Academy of Dermatology, 2013)
Direct immunofluorescence (DIF), indirect immunofluorescence (IIF), and enzyme-linked immunosorbent assay (ELISA) are used for the laboratory diagnosis of bullous pemphigoid (BP). The diagnostic value of DIF and IIF on rabbit and monkey esophagus or human salt-split skin and commercial ELISAs was assessed. This was a single-center retrospective study where 313 patients with BP were compared with 488 control subjects. DIF was the most sensitive test (90.8%) whereas sensitivities for IIF on rabbit esophagus, IIF on monkey esophagus, IIF on salt-split skin, BP180 ELISA, and BP230 ELISA were 76.0%, 73.2%, 73.3%, 72.0%, and 59.0%, respectively. The sensitivity of the serologic tests was 88.8% altogether. The specificities for DIF, IIF on rabbit esophagus, IIF on monkey esophagus, IIF on salt-split skin, BP180 ELISA, and BP230 ELISA were 98%, 96.5%, 97.1%, 100%, 94.1%, and 99.2%, respectively. The retrospective nature of study was a limitation. Correlation of diagnostic data with clinical manifestations or disease course was not possible. In suspected BP, both serologic tests and DIF have to be performed because of a sensitivity issue. Although the ELISAs had a relatively low sensitivity, the serologic tests altogether almost reached the level of sensitivity of DIF. The specificities of all assays were excellent.